AGENT-BASED FIRE-SPREADING MODEL IN A DENSE URBAN COMMUNITY - M. D. Asiddao (Copernicus Publications, 2021)
Metro Manila, home to twelve-million residents scattered in densely populated cities, grows its population at a rate of 1.21% annually. Areas of the metro occupied by residents falling under the poverty line have only been increasing in density per year, and have been prone to fire incidents. One such area, Barangay Addition Hills in Mandaluyong City, has fallen victim to two disastrous fires four years apart: in 2016 and 2020. This study aims to accurately model a portion of Barangay Addition Hills when a fire starts in one of the most densely populated blocks while observing firefighters responding to the incident. The agent-based model adapts features from (Wilensky, 2006)’s Fire model and is virtually simulated with the help of two-dimensional satellite images of the area. The fire-spreading algorithm incorporates solving the heat diffusion equation to determine ignition time of combustible materials per unit area. Firefighters have been incorporated into the model with the help of the Bureau of Fire Protection (BFP)’s Operational Procedures Manual to determine their expected behavior when responding to a fire alarm. Simulations were run on a per-incident basis to determine the total affected area, estimated affected families, and time for the fire to be put under control under varying densities, traffic conditions, firefighter response times and manpower.